Model Peningkatan Kinerja UKM Berbasis Orientasi Entrepreneur - -, Widodo (Department of Management, Faculty of Economics, Universitas Negeri Semarang, 2013)
This study aims to examine how the model variables cover innovation entrepreneur orientation, learning orientation, initiative, commitment, adaptability and organizational performance based on the research gap and SMEs phenomena that exists in Semarang. The method used in this research is quantitative method. The data were collected through interviews by conducting the focus group disscusion (FGD), study documentation, and participant observation. The respondents of this research is 135 managers of SMEs in Semarang. The analysis techniques for this study is Structural Equation Model (SEM) with AMOS software. The study result shows that the increase of SMEs performance in Semarang is influenced by the ability of adaptability which is built by the commitment on consensus.